Sentir, pensar y amar el mundo: Hacia una razón que siente y un corazón que comprende, un diálogo entre Hannah Arendt, María Zambrano y Simone Weil - Muñoz Rodríguez, Ivonne (2023)
The conjugation between reason and sensibility gives place to love in the scenario of philosophy to conceive the reconciliation with the world and the possibility of a social transformation lie upon the dignity of human life. For Hanna Arendt, Simone Weil, and Maria Zambrano, talking about Eros is a fundamental part to think about the reality of the social oppression, that apparently, only through a sort of miracle that we call love, it´s not destroy the soul nor the value of goodness. In this context sympathy and understanding as elements of the sensibility, make the existence itself possible, and give way for the love to the world to happen as something sacred and indestructible despite havoc cause by the violence that humanity suffers. The reason intertwined with the sensibility draws a pathway for human beings, that involves doing an ethical duty, of knowing to constitute oneself in community to build a compromise with the world, that is the loving pact that allows humanity reconciliation and transformation.